Polarization of Macrophages in Epidural Inflammation Induced by Canine Intervertebral Disc Herniation - Vizcaíno Revés, Núria; Mogel, Helga Maria; Stoffel, Michael; Summerfield, Artur; Forterre, Franck (Frontiers in Veterinary Science, 2020)
Introduction Canine interverterbral disc (IVD), although physiologically acellular, displays an inflammatory cell population consisting almost exclusively of macrophages (Mφ) when acutely herniated. Mφ encompass a heterogenous cell population, roughly divided into classically (M1) or alternatively activated (M2)Mφ. Polarization into M1 Mφ leads to strong antimicrobial activity and pro-inflammatory response. In contrast, M2Mφ exibit anti-inflammatory function and regulate wound healing. The purpose of this study was to characterize the phenotype of the Mφ population present in naturally occuring IVD herniation. Materials and Methods IVD material of dogs with IVD disease was collected during standard decompressive surgery. A negative control consisting of IVD material of dogs without IVD degeneration and a positive control consisting of canine liver and lymph node samples were also included. All samples were embedded in OCT and shock frozen. Eight micrometer cryostat sections were prepared, air dried and immunostained without prefixation or permeabilization. CD14 was used as marker Mφ, MHCII for M1Mφ and CD206 for M2Mφ. Results Fifteen samples of dogs with IVD herniation, 10 negative and 5 positive control samples were obtained. No positive cell was found in the negative control group. The positive control group displayed several MHCII and CD206 positive cells, all of them being simultaneously positive to CD14. All herniated samples displayed a mixed population of M1Mφ and M2Mφ, and some sparse Mφ displaying markers for both M1 and M2Mφ simultaneously. Conclusion The mixed phenotype encountered shows the plasticity and dynamism of Mφ and evidences the chronic component of IVD disease despite its acute clinical presentation.